Lactococcal Phage Genes Involved in Sensitivity to AbiK and Their Relation to Single-Strand Annealing Proteins - Bouchard, Julie D. (American Society for Microbiology, 2004)
Lactococcal phage mutants insensitive to the antiviral abortive infection mechanism AbiK are divided into two classes. One comprises virulent phages that result from DNA exchanges between a virulent phage and the host chromosome. Here, we report the analysis of the second class of phage mutants, which are insensitive to AbiK as a result of a single nucleotide change causing an amino acid substitution. The mutated genes occupy the same position in the various lactococcal phage genomes, but the deduced proteins do not share amino acid sequence similarity. Four nonsimilar proteins involved in the sensitivity to AbiK (Sak) were identified. Two of these Sak proteins are related to Erf and RAD52, single-strand annealing proteins involved in homologous recombination.